Education and Assessment: Prophecy or Prediction - Mónica Patricia Borjas (Universidad Nacional, Costa Rica, 2014)
This essay takes a critical look at the visions and realities of educational evaluation. It is based on two assumptions that describe different contexts that can be used to analyze assessment characteristics. Faced with these two contexts, readers can make their own predictions or prophecies about the future of this process, which is relevant to ensure the quality of learning processes in educational institutions.